Mammalian toxicology of insecticides - Marrs, Timothy C. (Cambridge, UK: The Royal Society of Chemistry, 2012)
Insects are more similar in structure and physiology to mammals than plants or fungi. Consequently, insecticides are often of greater toxicity to mammals than herbicides. This is particularly the case with neurotoxins. However, some insecticides are targeted at structures or hormonal systems specific to insects (insect growth regulators/chitin synthesis inhibitors) so are less harmful but can still be mildly haematotoxic. There are, therefore, issues specific to insecticides, which do not occur with other pesticides - hence the need for a book specifically on insecticide toxicology in mammals. The book starts with general issues relating to the mammalian toxicity of insecticides, including target/non-target specificity, nomenclature and metabolism of insecticides. It then goes on to discuss specific types of insecticides including: organochlorines; anticholinesterases; pyrethrum and synthetic pyrethroids; nicotine and the neonicotinoids; insect growth regulators/ecdysone agonists/chitin synthesis inhibitors; insecticides of natural origin; biological insecticides; and insecticides used in veterinary medicine. (Book back cover)
Keywords: Toxicology -- Mammals; Toxicology -- Insects; Insecticides